Application of Absorption Spectra to Study Order of Sequence in Intersecting Printed and Pen Strokes - Giri, R.; Chimouriya, S. P.; Ghimire, B. R. (Journal of Nepal Physical Society, 2022)
This work is performed to establish chronological order in crossing strokes between printed stroke and pen strokes. Nine different types of pens including cello maxriter pen (black and blue), pilot pen (red and black), cello pointec pen (black and blue) and cello techno tip pen (red, black and blue) are used to produce pen strokes and for printed stroke Canon LBP 3300 printer is used. In the case of printed stroke, only black color stroke is applied. As a result, samples of both homogeneous and heterogeneous intersecting strokes are prepared. This work is based on the assumption that nature and peak characteristics of absorption spectra from crossing stroke should be similar to that of second stroke. Here, absorption spectra is generated by Video Spectral Comparator-6000 by using light of wavelength ranging from 400 nm to 1000 nm. From this experiment, it is found to be possible to find chronological order for heterogeneous crossing strokes (crossing stroke of different colors) only if printed stroke is over pen stroke. It means, only if print is done over writing strokes from red and blue pen, then order of sequence of writing can be determined whereas in other cases it is not possible.